Matharpacady-16.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
The interiors at 20A Matharpacady are furnished with antique wooden furniture. The eclectic collection of curios displayed inside the vitrine were acquired from various corners of the world, reflecting the family's extensive travel history and maritime activities. The vitrine was meticulously crafted by a Chinese craftsman, specially summoned for this task, who made it in the confines of this home.